Meningoencephalocele associated with chromosomal mosaicism in a neonate canis familiaris - Guerrero, Ana E.; Chalco, Lorena; Pérez, Jhonny E.; Da Mota, Ligia S.L.S. [UNESP]; Nirchio, Mauro (Universidad Nacional Mayor de San Marcos, Vicerectorado de Investigacion, 2021)
The results of a cytogenetic study carried out in two female Miniature Pinscher who died after birth, one affected with meningoencephalocele (MEC) and the other apparently normal, are presented. The analysis of 156 metaphases (75 of the specimen with pathology and 81 without pathology) showed a typical unimodal female complement 2n = 78 (76, XX) in 95.06% of all metaphases in the normal puppy, while the puppy with ECM showed a multimodal karyotype with three chromosomally distinct cell lines: 2n = 78 (36%); 77 (28%); 76 (10.67%). The remaining 25.33% of cells corresponded to cells with less than 76 chromosomes. Statistical analysis of the medians of the chromosome counts using the Man-Whitney U test between the normal (median = 78; median range = 51.81) and affected (median = 77; median range = 26.69) puppies revealed highly significant differences (p=2.8192×10-13). It was not possible to establish a pattern that would allow to identify a specific aneuploidy but it was possible to verify that the numerical variation affected both the sex chromosomes and those of the first large acrocentric complement pair, as well as other remaining chromosomal elements, which suggests the occurrence of random non-disjunction processes in the cells of the MEC-affected puppy. This result constitutes the first evidence of association between a case of MEC and chromosomal mosaicism in dogs.
Meningoencefalocele asociado a mosaicismo cromosómico en un neonato Canis familiaris
Keywords: Canine; Defect; Karyotype; Neural tube; Veterinary